Formulation and Evaluation of Gastro Retentive Floating Microspheres of Nimodipine - Bakshi, Dr. Vasudha (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Nimodipine is a dihydropyridine calcium channel blocker developed for the treatment of high blood pressure. Nimodipine has a half-life of 8-9 h, the bioavailability of 13% and it has narrow absorption window in upper part of the gastrointestinal tract (GIT), hence floating drug delivery system (FDDS) is preferred. During the study, nimodipine encapsulated floating microspheres were formulated and characterized for enhancing residence time of drug in GIT. Materials and Methods: Floating microspheres of nimodipine with ethyl cellulose and Eudragit S100 were prepared by solvent evaporation method. Microspheres were characterized for their micromeritic properties, floating behavior, entrapment efficiency, scanning electron microscopy (SEM), X-ray diffraction, differential scanning calorimetry, and in vitro drug release. Results and Discussion: Floating microspheres were successfully prepared by solvent evaporation method. SEM images showed that microspheres prepared with different concentrations of polymer and emulsifier were spherical shaped with a smooth surface. The prepared microspheres also showed good flow properties. Size of microspheres was in the range of (90 Â± 1.02)-(145 Â± 1.34) Î¼m. Microspheres were capable to float for 12 h. As the polymer concentration increases in vitro drug release was decreased. However, the release was controlled by polymer concentration for a longer period. Conclusion: The optimized formulation showed good results for all the evaluation parameters. Hence, it can be concluded that the developed formulation is a potential dosage form for nimodipine.